2010
DOI: 10.1144/0071131
|View full text |Cite
|
Sign up to set email alerts
|

Natural fractures in some US shales and their importance for gas production

Abstract: Shale gas reservoirs are commonly produced using hydraulic fracture treatments. Microseismic monitoring of hydraulically induced fracture growth shows that hydraulic fractures sometimes propagate away from the present-day maximum horizontal stress direction. One likely cause is that natural opening-mode fractures, which are present in most mudrocks, act as weak planes that reactivate during hydraulic fracturing. Knowledge of the geometry and intensity of the natural fracture system and the likelihood of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…10A, B). Some of these are filled by calcite, and do not contribute to permeability but they are important planes of weakness that tend to be reactivated by hydraulically induced fractures (Gale and Holder, 2010;Gale et al, 2007;Gasparrini et al, 2014). Some of the open fractures ( Fig.…”
Section: Micro-fracturesmentioning
confidence: 99%
“…10A, B). Some of these are filled by calcite, and do not contribute to permeability but they are important planes of weakness that tend to be reactivated by hydraulically induced fractures (Gale and Holder, 2010;Gale et al, 2007;Gasparrini et al, 2014). Some of the open fractures ( Fig.…”
Section: Micro-fracturesmentioning
confidence: 99%
“…Possible weak zones in the Barnett Shale include natural fractures and the newly created hydraulic fractures. Two sets of dominant natural fractures were reported to be in the westnorthwest and north-south directions, respectively (Gale et al, 2007;Gale and Holder, 2010). Finally, for reservoirs with a low horizontal differential stress and in normal faulting regimes, such as the Barnett Shale reservoir, rock failure could occur along almost any strike direction.…”
Section: Mean Absolute Errors In the Inverted Source Parametersmentioning
confidence: 99%
“…From core studies, two major sets of natural fractures were identified. One fracture system had an azimuth of north-south (north-south) and another, west-northwesteast-southeast (west-northwest) (Gale et al, 2007;Gale and Holder, 2010). The natural fractures in the Barnett Shale are completely healed and filled with calcites.…”
Section: Field Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Formations that have been identified as having at least 20 trillion cubic feet (tcf) of shale gas include the Marcellus Shale (410 tcf), the Antrim Shale (20 tcf), the Haynesville Shale (75 tcf), the Eagle Ford Formation (21 tcf), the Fayetteville Shale (32 tcf), the Barnett and Woodford Shales (97 tcf), and the Mancos Shale (21 tcf). Many of these units are not shales in a strict sense, but may be better described as siliceous mudstones with reduced clay contents; these slightly brittle rocks can be subjected to successful hydrofracture treatment (Gale and Holder, 2010). While many areas within these sedimentary basins are sites of active and prospective oil and gas exploration and The data used for this report represent information that was either digitized using ArcGIS from published isopach and structure maps, or was available as GIS shape files that delineate formation isopachs and structural surfaces relative to a known datum, such as sea level or the ground surface.…”
Section: Data Sourcesmentioning
confidence: 99%